Social Movement in Pengajian at Jogokariyan Mosque - Ahmad Muttaqin (Jurnal Living Hadis, 2019)
Pengajian (religious teaching) is one of the primary programmes at Jogokariyan mosque. It has been held regularly and incidentally using the current issues as a theme. After the 212 demonstration 2016 in Jakarta, pengajian in Jogokariyan always uses the specific themes related to the religious social issues.  This article tries to explore how the reception of hadis or the teachings of prophetic tradition live in a social movement in the context of pengajian at Jogokariyan mosque. Employing a social movement approach, this article seeks to explore deeply how the hadis or prophetic traditions are expressed and its relevance to the social movement in pengajian. The social movement has three strategies, namely, (1) political opportunities, (2) mobilizing structures and (3) framing process. This present paper concludes that firstly, religious teaching in Jogokariyanmosque is a model of reception of hadis about seeking knowledge and majlis ilm’. The hadis is used as a basic tool to mobilize the process of social movement in pengajian. Secondly, the social movement in the Jogokariyan mosque is motivated by the injustice feeling caused by the policy of the government today.